The Effect of Profitability, Company Size and Capital Structure on Stock Prices in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange - Novita, Reni Desti; Djazuli, Abid; Choiriyah, Choiriyah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
This study aims to determine the effect of Profitability, Company Size, and Capital Structure on Stock Prices in Consumer Goods Industrial Sector Companies Listed on the Indonesia Stock Exchange (IDX). The type of research used is descriptive research and verification research. The data used in this study is secondary data obtained from the IDX official website (www.idx.co.id). Methods of data collection using the form of documentation. The data analysis used is quantitative analysis. The analysis technique is multiple linear regression. The results of the joint study of profitability, firm size, and capital structure variables have a significant positive effect on stock prices in consumer goods industrial sector companies listed on the Indonesia Stock Exchange. Profitability and firm size have a significant positive effect on stock prices, while the capital structure significantly negatively impacts stock prices.